2017
DOI: 10.1186/s12909-017-1063-4
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating patient partner scores into high stakes assessment: an observational study into opinions and attitudes

Abstract: BackgroundVolunteer patients (also known as patient partners (PPs)) play a vital role in undergraduate healthcare curricula. They frequently take part in objective structured clinical examinations (OSCE) and rate aspects of students’ performance. However, the inclusion and weighting of PP marks varies, while attitudes and opinions regarding how (and if) they should contribute towards the pass/fail outcome are uncertain.MethodsA prospective observational study was conducted to explore beliefs of PPs regarding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Another interesting study also suggested regarding SP's opinion and attitude towards incorporating SP's score into summative assessment [7]. 60% of the SPs perceived that their marks should incorporated into the examination, however 70% of the SPs stated that candidate should not fail for those achieve low SP score but students can be remedial for the poor interpersonal skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting study also suggested regarding SP's opinion and attitude towards incorporating SP's score into summative assessment [7]. 60% of the SPs perceived that their marks should incorporated into the examination, however 70% of the SPs stated that candidate should not fail for those achieve low SP score but students can be remedial for the poor interpersonal skills.…”
Section: Introductionmentioning
confidence: 99%
“…60% of the SPs perceived that their marks should incorporated into the examination, however 70% of the SPs stated that candidate should not fail for those achieve low SP score but students can be remedial for the poor interpersonal skills. SPs expressing that they have the responsible to assess communication skills, attitudes, professionalism, and interpersonal skills [4,5,7]. At the same time, SPs were also concerned of consistency among the SPs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, poor interpersonal skills could be remedied, whereby SPs expressed that they have the responsibility to assess communication skills, attitudes, professionalism, and interpersonal skills. At the same time, SPs were also concerned with consistency among the SPs (9). A few articles also informed regarding SPs' view between 'good' and 'bad' consultation.…”
Section: Evaluation Of Sp's Performancementioning
confidence: 99%
“…SP is regarded as an expert to comment upon students' certain aspects such as communication skills (9,16) and empathy (18) due to SPs are directly in the clinical encounter and therefore likely to be in a position to assess such skills (9,18) as well as the institution acknowledge the ability of SPs to effectively assess trainees' communication skills and interpersonal skills (9). Few studies had confirmed the reliability and validity of SP's evaluation.…”
Section: Evaluation Of Students' Performancementioning
confidence: 99%
“…[5] Previous research has clarified the process by which lay residents master the task of role-playing a patient [6] and the opinions and attitudes of Simulated Patients. [7] However, the existing research has not adequately examined the significance that participatory SPEs hold for the local residents who act as Simulated Patients.…”
Section: Introductionmentioning
confidence: 99%